Implementasi Nilai-Nilai Etika Sosial dalam Surat Al-Hujurat Ayat 11 pada Masyarakat Modern - Jadidah, Nur (Maliki Interdisciplinary Journal, 2025)
Surah Al-Hujurat verse 11 contains the principles of social ethics which are very important for modern society, especially in terms of building harmonious relationships and mutual respect. The behavior of making fun of, giving bad names, and planning evil against other people, both in person and online, is prohibited according to this verse. These social ethical values ​​are important because social challenges are increasingly complex in modern society, such as conflicts caused by social, cultural differences and unwise use of social media. These values ​​teach in a multicultural and pluralistic society how important it is to be tolerant, empathetic and respect differences. So, by practicing the teachings of Surah Al-Hujurat verse 11 every day, you can build a more peaceful, harmonious and loving society.